The place of graphic design in national development - Dzakpasu, Bridget Eli (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the award of the Degree of Master of Arts in Art Education.